A prospective cohort study on the role of nonspecialist staff in preventing relapses and improving clinic attendance of patients with schizophrenia - Rodrigo, Chaturaka (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The Sri Lankan government employs graduates from local universities (trained in nonpsychiatry disciplines) as Mental Health Development Officers (MHDOs) to fulfill the role of a psychiatric social worker. MATERIALS AND METHODS: This was a prospective interventional cohort study on preventing relapses of schizophrenia by active involvement of MHDOs. The intervention (randomly selected) and control groups each had 25 follow-up patients with schizophrenia (1:1 match for sex, ethnicity, age, and duration of illness). The intervention was to develop a close liaison with the patient/family and build an individualized client oriented follow-up through the MHDOs. The follow-up period was 1 year. RESULTS: The intervention group had better clinic attendance, less relapses, and defaults. The number needed to follow-up to avert a relapse or a default was 12.5 and 5 respectively. CONCLUSIONS: Low-cost strategies involving nonspecialist staff can reduce relapses and defaults in patients with schizophrenia.